Sexe on-line. Animateurs, clients et production de scénarios sexuels - Elena Stoian (Genre, Sexualité et Société)
In this article, the author aims at presenting both the practical and the discursive logic structuring sexual intercourse via erotic hotlines. Firstly, what are described are the working conditions of the professional moderators on these websites, male and female service providers, working in Romania. These employees are constrained by a set of professional rules, which structure the exchanges and aim at maximising the economic profitability of the connexions. The article then analyses part of an erotic dialogue, in order to think sexual exchanges. The relationships are read as discourses, mobilising some conventional sexual scripts, set in a temporality which extends into the virtual order the organisation of the so-called “real” exchanges (excitement, plateau, orgasm, resolution). And by taking hold of the techniques used by the protagonists to produce and organise such exchanges – from the consumer’s as well as the professional moderator’s point of view – the article equates erotic dialogue to sexual work, in which meaning can be found, by combining conversation analysis and sexual scripts theory.